ORGANIZATIONAL DESIGN AND CHANGE. THE EVOLUTION OF TRADE UNIONS ORGANIZATION FORMS IN ROMANIA AFTER 1989 - LUMINIŢA CRISTINA CIOCAN (Challenges of the Knowledge Society, 2012)
The study: „Management and organizational change. Evolution of union organization forms in Romania after 1989” propose as subject of analyze a type of organization which, through its affiliation to the civil society and through its role conferred by low, becomes the key for the proper functioning of the labor market. Along with the change of political regime from December 1989, the trade union organizations were put in a position to cope with a triple: reorganization, learning a new social role and public image reconfiguration, including cancellation of the association (inevitable) with the “ancient” trade union. The study proposes three major subjects: defining the term union organization accompanied by possible interpretations of the role of this type of organization at the society level – „collective voice”, counter pole , political actor, collective negotiator, transnational and promoter of the class struggle, the last role not being characteristic to a democratic society; the description of the syndicate organizations evolution in Romania, after 1990; the argue of the necessity of an organizational change felt by the unions, under the impact of some factors depending on socio-economic and politic changes.